21/#810 A current perspective on endometrial carcinoma (EC) risk classification: results from an European multicentre initiative. (4th December 2022) - Rohner, Annika; Grube, Marcel; Knoll, Katharina; Lum, Amy; Brambs, Christine; Pauly, Nina; Kommoss, Felix; Heublein, Sabine; Battista, Marco Johannes; Mittelstadt, Suzana; Praetorius, Teresa; Hasenburg, Annette; et al.
Abstract : Objectives: EC management has been plagued by poor interobserver reproducibility of histomorphologic features for a long time. More recently integration of TCGA-inspired molecular classification into pathology reporting and treatment guidelines was recommended. It was the aim to investigate the impact of adding molecular classification to a patient cohort diagnosed in an era before molecular classification was introduced to routine practice. Methods: Consecutive primary EC patients diagnosed in five major European gynonc centres in 2016 were identified and retrospectively submitted to molecular testing. Original risk classification ('RC16', ESMO/ESTRO/ESGO 2016) was compared to current molecular-based risk assessment ('RC20', ESGO/ESTRO/ESP 2020). Results: 226 patients were identified, complete clinical and molecular data was available from 212 cases with a median follow-up time of 52.6 months. Median age was 65.0 years (30.9–90.9), 187 cases (88, 2%) were endometrioid histotype. Grading included 92(43, 4%) G1, 72(34.0%) G2, and 47(22.2%) G3 tumors. 107(50.5%) patients were diagnosed with FIGO stage IA, 55(25.9%) with IB, n=17(8.0%) with II, and 33(15.6%) with stage III/IV disease. Molecular classification yielded 46(21.7%) MMR-D, 18(9.0%) POLE, 47(22.2%) p53abn, and 100(47.2%) NSMP tumors. If RC16 was compared to RC20, an alteration of risk was observed in 20.2% with a higher risk in 16(7.5%) and lower risk in 27(12.7%) respectively. Conclusions: We were able to demonstrate significant alterations of endometrial carcinoma risk-assessment in a substantial number of patients after adding TCGA-derived molecular data to conventional risk classification. Molecular based management may help to avoid over- and undertreatment and will give rise to precision medicine strategies in endometrial carcinoma patient care.